Aplicación de argireline con técnica de micropunción en tratamientos preventivos de envejecimiento en paciente de 37 años - Espinel Mena, María Belén (2025)
This case study focuses on identifying the effectiveness of facial rejuvenation through the application of Argireline with microneedling technique. The objective of the study was to verify the benefits of Argireline. The methodology used was divided into different stages such as: patient selection, initial assessment, development of the treatment sessions, assessment in each session, analysis of the results, conclusions, recommendations and presentation of the project. Argireline applied with Dermapen is a component known for its ability to reduce wrinkles and expression lines. It works by inhibiting muscle contraction, which can help smooth the appearance of the skin and improve its texture. The study analyzes the effectiveness of Argireline in the facial area with microneedling. Eight sessions were carried out every 15 days, during which the vitality of the skin, the attenuation of wrinkles, the hydration of the lips, the unification of the tone, the attenuation of solar lentigines, the reduction of sagging, the attenuation of the nasolabial and nasolabial folds, as well as restoring the properties of the skin and stimulating the production of collagen and elastin were observed. Although the different signs were not completely eliminated, a notable decrease in them was observed. In conclusion, Argireline is considered an effective component that helps improve the appearance of the skin by reducing wrinkles and stimulating collagen production. The indications and recommendations were followed in the treatment, and no complications or adverse reactions occurred.